DIRECTIVES ON COMMUNITY USE OF FACE MASKS DURING COVID-19 PANDEMIC: A COMMENTARY ARTICLE - Dilip H Liyanage; Pamila Sadeeka Adikari; KGRV Pathirathna; WDCU Dias (Universitas Airlangga, 2021)
Wearing a universal face mask is recommended by most health authorities during the COVID-19 pandemic. This commentary elaborates directives given in relation to the use of face masks and identify the underlying principles for public health recommendations by the government authorities of Australia, Canada, China, Hong Kong, Singapore, the United Kingdom and the United States of America. Key data were considered from official government websites by a team of healthcare management experts. It was argued that the directives recommended by the governments were based on the principles addressing the different facets of COVID-19 pandemic, population dynamics, resource availability and scarcity, and the fact that how the proposed standard of practices would be translated into compulsory obligations in the community. The principles involved regulations versus voluntary compliance of the population, transmission scenario, protection from sick or asymptomatic people, special needs and vulnerable groups, synergistic versus substitute/alternative, occupational health risk, adverse effects on usage, types of masks which depend on the risk or context, change in use practices depending on demand, scarcity and quality assurance. Recommendations of the use of face masks were found to be heterogeneous and apparently inconstant. Within the dynamic situation of the COVID-19 pandemic, the directives on community use of face masks were issued based on certain dominant principles and interplayed between principles that should be deeply explored by the healthcare decision makers. Keywords: COVID-19, face masks, pandemic, public health measures